PARALLEL SESSIONS AT ICOLLT 4.0 2024 A TRIUMPH IN COLLABORATION AND INNOVATION - Rosnani, Ismail; Ezihaslinda, Ngah (Pusat Bahasa Moden (PBM), 2024)
The International Conference on Language Learning and Teaching (ICoLLT) 4.0 2024 was successfully held on May 20-21, 2024, at Perdana Hotel in Kuala Lumpur. Organised by Centre for Modern Languages, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Malaysia, in collaboration with Universitas Ahmad Dahlan (UAD), Thailand, and Ho Chi Minh City University of Technology (HCMC), Vietnam, the conference brought together scholars and researchers from across the region.